Cu(I) coordination polymer based on pyridyl-functionalized resorcin[4]arene: Selective detection of Cr2O72−, MnO4− and nitrobenzene and efficient catalyst for azide–alkyne cycloaddition reaction. (15th January 2019) - Liu, Yan-Li; Yan, Lei; Liu, Ying-Ying; Xu, Guo-Hai; Shi, Wen-Jing; Ma, Jian-Fang
Graphical abstract: In this work, a Cu(I) coordination polymer constructed by a novel pyridyl-functionalized resorcin[4]arene and CuBr2 has been synthesized and structurally characterized. It can selectively detect Cr2 O7 2−, MnO4 − and nitrobenzene via luminescent quenching and effectively catalyse azide–alkyne cycloaddition reaction. Abstract: In this work, a novel Cu(I) coordination polymer, Cu2 LBr2 (1 ) based on a pyridyl-functionalized resorcin[4]arene [L = (2, 8, 14, 20-tetraethyl-4, 10, 16, 22-tetra kis((2-pyridylmethylene)oxy)-6, 12, 18, 24-tetramethoxy-resorcin[4]arene)] has been synthesized under solvothermal condition.1 was characterized by various physicochemical analyses and it shows a ribbon structure. Notably, 1 exhibits an outstanding thermal stability.1 possesses strong luminescent property, and can selectively probe Cr2 O7 2−, MnO4 − and nitrobenzene via luminescent quenching. In addition, 1 is an efficient catalyst for azide–alkyne cycloaddition reaction.